KARAKTERISTIK UMUM DIATOM DAN APLIKASINYA PADA BIDANG GEOSAINS - Septriono Hari Nugroho (OSEANA, 2019)
AN OVERVIEW OF DIATOM AND ITS APPLICATIONS ON THE GEOSCIENCE AREA. Diatoms have been being studied in many countries. Diatoms provide a valuable and well-understood means on biomonitoring – one of which is focused on the base of the aquatic foodweb and highly representative of water quality. They are found in most aquatic environments and the sys tematic and taxonomic investigations of modern and fossil diatoms have been supported by numerous stud ies of distributional ecology. Diatom systematics, taxonomy and ecology indeed offer a wide scope of applications - from water quality to environmental monitoring and biostratigraphy as well as on geoscience area. The application of diatom analysis in determining whether drowning was the cause of death has proven to be a valuable tool in forensic science. Furthermore, diatoms can provide a record of environmental conditions because their relationship to water quality and aquatic habitat has been already known, and the diatom cell wall, which is silicified to form a frustule, is well-preserved, easily detectable and occurs in high numbers in sediment and water. However, this should not be limited to simply make an inventory of data: thoughtful ecology and paleo-ecology will assist in predicting the environmental impact of pollution and climate changes.